The Optimum Parameters for Material Flow Speed, Working Noise, and Material Flow Direction for Physical and Mental Workload - Ansori, Nachnul; Widiaswanti, Ernaning; Krestiyanto, David (Management and Production Engineering Review, 2026)
Conveyor equipment is commonly used in packaging systems, and operators must stand for long periods and perform a similar, monotonous task. This might increase the operator’s physical and mental fatigue. A hypothesis is, that the speed, noise, and direction of material flow influence the operator’s workload. A work system optimization could be proposed using response surface methodology. The Central Composite Design was proposed as an experimental design. Both physical and mental workload are assessed as the response. The results showed that the optimal combination of physical workload response parameters was a speed of 25.8579 cm/s, a noise of 89.3569 dB, and a flow direction from right to left. Meanwhile, the optimal parameter combination for mental workload response was a speed of 25.8579 cm/s and a noise level of 77.9289 dB, with the most optimal flow direction from right to left.